2015
DOI: 10.1155/2015/673716
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Scalar Fields Oscillons and Breathers in Some Lorentz Violating Scenarios

Abstract: We discuss the impact of the breaking of the Lorentz symmetry on the usual oscillons, the so-called flat-top oscillons, and the breathers. Our analysis is performed by using a Lorentz violation scenario rigorously derived in the literature. We show that the Lorentz violation is responsible for the origin of a kind of deformation of the configuration, where the field configuration becomes oscillatory in a localized region near its maximum value. Furthermore, we show that the Lorentz breaking symmetry produces a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 79 publications
(121 reference statements)
0
1
0
Order By: Relevance
“…In fact, they have shown that these new oscillons are more robust against collapse instabilities in three spatial dimensions. In a recent work, the impact of the Lorentz and CPT breaking symmetries was discussed in the context of the so-called flat-top oscillons [14].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, they have shown that these new oscillons are more robust against collapse instabilities in three spatial dimensions. In a recent work, the impact of the Lorentz and CPT breaking symmetries was discussed in the context of the so-called flat-top oscillons [14].…”
Section: Introductionmentioning
confidence: 99%